A Complex Intervention to Prevent Medication-Related Hospital Admissions - Neubert, Antje; Toni, Irmgard; König, Jochem; Urschitz, Michael S.; Rascher, Wolfgang (Deutsches Ärzteblatt international, 2023)
BACKGROUND: Children are often treated off-label and are at a disadvantage in pharmacotherapy. The aim of this study was to implement and evaluate a quality assurance measure (PaedPharm) for pediatric pharmacotherapy whose purpose is to reduce medication-related hospitalizations among children and adolescents. METHODS: PaedPharm consisted of the digital pediatric drug information system PaedAMIS, pediatric pharmaceutical quality circles (PaedZirk), and an adverse drug event (ADE) reporting system (PaedReport). The intervention was implemented in a cluster-randomized trial (DRKS 00013924) in 12 regions, with a pediatric and adolescent medicine clinic in each and a total of 152 surrounding private practitioners, in 6 sequences over 8 quarters. In addition to the proportion of ADE-related hospital admissions (primary endpoint), comprehensive process evaluation included other endpoints such as coverage, user acceptance, and relevance to practice. RESULTS: 41 829 inpatient admissions were recorded, of which 5101 were patients of physicians who participated in our study. 4.1% of admissions were ADE-related under control conditions, and 3.1% under intervention conditions (95% CI: [2.3; 5.9] and [1.8; 4.5], respectively). A model-based comparison yielded an intervention effect of 0.73 (population-based odds ratio; [0.39; 1.37]; p = 0.33). PaedAMIS achieved moderate user acceptance and PaedZirk achieved high user acceptance. CONCLUSION: The introduction of PaedPharm was associated with a decrease in medication-related hospitalizations that did not reach statistical significance. The process evaluation revealed broad acceptance of the intervention in outpatient pediatrics and adolescent medicine.
CRIS-Team Scopus Importer:2023-09-15